IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT THROUGH LANGUAGE EXPERIENCE APPROACH AT THE EIGHTGRADE STUDENTS OF SMP NEGERI 1 LOLOMATUA - M. Yunus Laia (Jurnal Education and Development, 2018)
This researchaimed to improve the Student’s ability in writing descriptive text through Language Experience Approach (LEA). This research was designed by using Classroom Action Research (CAR) which was done in two cycles. Incollecting the data, observation paper and test were usedas the research instruments. Based on the data analysis,showed that the result of the observation paper of researcher’s activities in meeting I was 68,75 % while meeting II was 81,25% and cycle II in the first meeting was 87,5% while in the second meeting was 93,75%. While the result of students’ observation paper of students activities in cycle I in meeting I was 78,9% while in second meeting was 79,1% and cycle II in the meeting I was 83,2% while in the meeting II was 87,6%. The students’ test result in cycle Iwas 59,5%while in cycle II was 75,46%.Based on the research findings, in implementing Language Experience Approach (LEA) in teaching writing more interesting, effective and efissien in learning English especially in descriptive text. The researcher suggested that the teacher isexpected to teach writing descriptive text through application of Language Experience Approach (LEA) because through this approach, the students’ ability in writing decriptive text can be improved.